PENGARUH PRICE TO BOOK VALUE, EARNINGS PER SHARE, DAN UMUR PERUSAHAAN TERHADAP HARGA SAHAM PADA PT SEMEN BATURAJA (PERSERO) TBK PERIODE 2015-2024 - Hia, Beatus Bewamati; Nugroho, Riski Dwi (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. This study aims to analyze the effect of Price to Book Value (PBV), Earnings Per Share (EPS), and company age on stock prices at PT Semen Baturaja (persero) Tbk for the period 2015-2024. This study uses a descriptive method with a quantitative approach. All data used are secondary data obtained from the annual financial statements of PT Semen Baturaja (persero) Tbk, namely the financial position report and profit and loss report that are officially published. Data analysis techniques used are starting from the classical assumption test, multiple linear regression, the feasibility test of the F test model, to the partial t test, with the help of E-views software. The results of the study indicate that PBV is proven to have a significant effect on stock prices, with a calculated t-value of 42.33174 > t-table of 2.447 and a significance level of 0.0000 which is far below the significance limit of 0.05. Conversely, EPS does not show a significant effect because it has a significance value of 0.1676. Similar results also occur in the company age variable which obtains a significance value of 0.6555. In other words, individually, only PBV is able to statistically explain stock price changes in this study. The calculated F-value of 934.8821 is proven to far exceed the F-table of 4.76, and the significance level is 0.000000. This finding indicates that PBV, EPS, and company age simultaneously have a significant influence on stock prices, although partially only PBV is dominant. The coefficient of determination is seen from the Adjusted R-squared value of 0.996798. This figure indicates that approximately 99.68% of stock price variations can be explained by the combination of these three variables. The remaining 0.32% is influenced by other factors outside the model that were not examined in this study.